Evolving Viscous Anisotropy in the Upper Mantle and Its Geodynamic Implications. (25th September 2020) - Király, Á.; Conrad, C. P.; Hansen, L. N.
Abstract: Asthenospheric shear causes some minerals, particularly olivine, to develop anisotropic textures that can be detected seismically. In laboratory experiments, these textures are also associated with anisotropic viscous behavior, which should be important for geodynamic processes. To examine the role of anisotropic viscosity for asthenospheric deformation, we developed a numerical model of coupled anisotropic texture development and anisotropic viscosity, both calibrated with laboratory measurements of olivine aggregates. This model characterizes the time‐dependent coupling between large‐scale formation of lattice‐preferred orientation (i.e., texture) and changes in asthenospheric viscosity for a series of simple deformation paths that represent upper mantle geodynamic processes. We find that texture development beneath a moving surface plate tends to align the a axes of olivine into the plate motion direction, which weakens the effective viscosity in this direction and increases plate velocity for a given driving force. Our models indicate that the effective viscosity increases for shear in the horizontal direction perpendicular to the a axes. This increase should slow plate motions and new texture development in this perpendicular direction and could impede changes to the plate motion direction for tens of millions of years. However, the same well‐developed asthenospheric texture may foster subduction initiation perpendicular to the plate motion and deformations related to transform faults, as shearing on vertical planes seems to be favored across a sublithospheric olivine texture. These end‐member cases examining shear deformation in the presence of a well‐formed asthenospheric texture illustrate the importance of the mean olivine orientation, and its associated viscous anisotropy, for a variety of geodynamic processes. Plain Language Summary: The uppermost layer of Earth's mantle, the asthenosphere, experiences large deformations due to a variety of tectonic processes. During deformation, grains of olivine, the main rock‐forming mineral in the asthenosphere, rotate into a preferred direction parallel to the deformation, developing a texture that can affect the response of the asthenosphere to tectonic stresses. Laboratory measurements show that the deformation rate depends on the orientation of the shear stress relative to the olivine texture. We use numerical models to apply the findings of the laboratory measurements to geodynamic situations that are difficult to simulate in a laboratory. These models track the development of olivine texture and its directional response to shear stress, which are highly coupled. Our results suggest that anisotropic viscosity in the asthenosphere can significantly affect the motions of tectonic plates, as plate motion in a continuous direction should become faster, while abrupt changes in the direction of plate motion should meet high resistance in the underlying asthenosphere. We suggest that olivine textures in the asthenosphere play a critical role in upper mantle dynamics. Key Points: We develop models of olivine texture evolution within deforming asthenosphere, and the associated directional variations in viscosity The effective viscosity of textured olivine can vary by an order of magnitude, depending on which slip system dominates the deformation Anisotropic viscosity promotes faster plate motion and ridge‐parallel subduction initiation but impedes directional changes in plate motion